If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -2j = 4 Solving 12 + -2j = 4 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2j = 4 + -12 Combine like terms: 12 + -12 = 0 0 + -2j = 4 + -12 -2j = 4 + -12 Combine like terms: 4 + -12 = -8 -2j = -8 Divide each side by '-2'. j = 4 Simplifying j = 4
| 49x^2+101x=-67 | | -16=-4u+2(u-5) | | 7(7)-6(5)= | | 49x^2+101x+67=0 | | 7(-4)-6(0)= | | 5(3c-2)=40-2c | | 8+41nx=3 | | -33=-7(2)-3 | | b-2.25=1 | | 3(-4x-4)=5+1x | | 9(3)+2(-7)= | | 9(0)+2(-8)= | | 2y+(y-3)+3=7y-(2y+4) | | 5x+17=4(3x+1) | | 145=-u+220 | | 9(4)+2(-5)= | | =1.2 | | 49-w=232 | | 3a+5b+11b-4b+2a-6= | | x+8y^3=0 | | 9y-(5y-4)=10y-(3y+2) | | inx^3=6 | | 45x-37y+87= | | 17-2p=4p | | 12x-11=64 | | -7(-6+9f)+3= | | 79-13= | | 9(-4z+5)-8= | | 3z^2-0.75=90 | | x+9=4(x-1)(x-1) | | 7+13x=11+13x | | 3(6x+8)=9x-16-x |